PENETAPAN KADAR PROTEIN JAMUR TIRAM PUTIH (Pleurotus ostreatus) DAN JAMUR MERANG (Volvariella volvaceae) DENGAN METODE KJELDAHL - Dara Callista Dinda Amelia; Diah Astika Winahyu (Jurnal Analis Farmasi, 2022)
Mushrooms are plants that contain high levels of vitamin B complex and are the only non- animal foods with vitamin D content that are used for bone health.White oyster mushrooms and straw mushrooms have a lot of nutritional content, one of which is protein. Proteins are complex organic compounds of high molecular weight. Quantitative testing with the Kjedahl method has three stages, namely destruction, distillation, and titration. The results of the quantitative test using the Kjedahl method showed that oyster mushrooms had a protein content of 2.39% and straw mushrooms were 1.46%.